Breast cancer in very young women—a multicenter 10-year experience - Eiriz, I.F.; Vaz Batista, M.; Cruz Tomás, T.; Neves, M.T.; Guerra-Pereira, N.; Braga, S. (My University, 2021)
Background: Breast cancer (BC) is the most prevalent cancer in adult young women in Europe. Although rare, it is one of the leading causes of death in this age group. The aim of this study is to characterize a cohort of young women regarding tumor stage, biology, treatment and survival. Patients and methods: We present a multicenter retrospective analysis of women <35 years of age, diagnosed with BC between 2008 and 2017. A total of 207 patients from five Portuguese centers were included, from whom 172 were eligible for analysis. Data were analyzed using IBM SPPSS statistics. Results: Median age at diagnosis was 31 years. Fifty-one percent of tumors were hormone receptor (HR)-positive/human epidermal growth factor receptor 2 (HER2)-negative, 20% HR-positive/HER2-positive, 8% HR-negative/HER2-positive and 20% triple-negative BC. Twenty-two percent of patients were diagnosed in stage I, 26% stage II, 45% stage III and 6% had de novo metastatic cancer. Thirty-nine percent of patients were treated with neoadjuvant chemotherapy. Mean follow-up time was 64.9 months and overall survival at 5 years, of the entire cohort and metastatic patients, was 86.5% and 26%, respectively. Conclusions: In our study we found similar population characteristics to other cohorts <35 years of age. To our knowledge, this is one of the largest cohorts in very young women. BC in young women is an important issue and further studies are needed to provide better care and survivorship to patients.
Keywords: breast cancer; young women